What methods are currently available to prevent and treat antibiotic-associated diarrhoea in children? - E. V. Kanner; A. V. Gorelov; M. L. Maksimov; A. S. Ermolayeva; I. S. Bulgakova (Медицинский совет, 2020)
Unwanted drug reactions of the gastrointestinal tract (GIT), often with the development of antibiotic-associated diarrhoea (AAD), are the most frequent adverse effects of antibacterial therapy in outpatient practice. This review presents the most current data on antibiotic-associated intestinal lesions. It provides up-to-date information on the epidemiology and etiology of microbial factors of AAD and pseudomembranous colitis.The authors cite clinical forms of AAD, which range from idiopathic with a picture of enteritis to pathogen-specific AAD (antibiotic-associated colitis). A comprehensive approach to AAD verification and patient management tactics makes it possible to significantly reduce the number and severity of possible complications. AAD, including C. difficile-associated diarrhoea/colitis, should be suspected in any patient with diarrhoea who has received antibiotics in the previous 2 months. In addition to clinical signs, laboratory tests confirming clostridial infection should be evaluated. The article presents the algorithm of the comprehensive approach to the treatment of antibiotic-associated diarrhea (AAD), which along with the use of metronidazole and vancomycin places a high priority on the probiotics, which not only prevents relapse, but also protects from this pathology.The article presents general characteristics of probiotic preparations, mechanisms of action of probiotics: antagonistic influence on pathogenic and opportunistic bacteria of microbiota, strengthening of mucous barrier of gastrointestinal tract, and also influence on modulation of immune response, as a result of which the chain of mechanisms of immunological protection starts. On the basis of publications of domestic and foreign researchers, the possibilities of using various probiotic strains of bacteria, and in particular, the prospects of using Lactobacillus reuteri, have been considered.